Increased Aurora B expression reduces substrate phosphorylation and induces chromosomal instability - Britigan, Eric M. C.; Wan, Jun; Sam, Daniel K.; Copeland, Sarah E.; Lasek, Amber L.; Hrycyniak, Laura C. F.; Wang, Lei; Audhya, Anjon; Burkard, Mark E.; Roopra, Avtar; Weaver, Beth A. (Frontiers in Cell and Developmental Biology, 2022)
Increased Aurora B protein expression, which is common in cancers, is expected to increase Aurora B kinase activity, yielding elevated phosphorylation of Aurora B substrates. In contrast, here we show that elevated expression of Aurora B reduces phosphorylation of six different Aurora B substrates across three species and causes defects consistent with Aurora B inhibition. Complexes of Aurora B and its binding partner INCENP autophosphorylate in trans to achieve full Aurora B activation. Increased expression of Aurora B mislocalizes INCENP, reducing the local concentration of Aurora B:INCENP complexes at the inner centromere/kinetochore. Co-expression of INCENP rescues Aurora B kinase activity and mitotic defects caused by elevated Aurora B. However, INCENP expression is not elevated in concert with Aurora B in breast cancer, and increased expression of Aurora B causes resistance rather than hypersensitivity to Aurora B inhibitors. Thus, increased Aurora B expression reduces, rather than increases, Aurora B kinase activity.